Przysłowia ludowe i ich kontekst kulturowy w odniesieniu do żywności i żywienia w arabskich dialektach Āzaẖ i Mārdīn - Abdalla, Michael (Investigationes Linguisticae, 2015)
This draft is an attempt to group and analyze the content of maxims, expressions, utterances, phrases, aphorisms and formulations which refer – directly or indirectly – to agriculture and raising animals as well as to the widely understood traditions and the culture of feeding among the inhabitants of the two ancient Assyrian towns in southeastern Turkey: Āzaẖ and Mārdīn. This type of folk prose is very popular in the Middle East. Even though the procurement of food and the preparation of meals belong likely to the most important human cares and take most of the time particularly of the populations living in villages, the group of proverbs concerning the analyzed topic in each collection is only about 8% of the total.